the effects of family violence on the deviant behavior among government middle school students in the province of Al- Taif - Al-Ghamdi, Mohammed Ahmed (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed at evaluate the effects of family violence on the deviant behavior among government middle school students in the province of Taif. The Researcher followed the descriptive approach in applying the study on a sample of 189 students who were selected by using simple intentional selection sampling from four middle schools that represented various neighborhoods in the Province to ensure their representation of the study population.  Survey forms were distributed and 193 answered forms were collected, 6 were excluded due to lack of completion thus resulting in 187 valid forms for analysis. Data were entered and analyzed by the SPSS. Results showed no correlation between the types of family violence and deviant behavior among the sample, although some reported the observation of fights among sibling.  The results also showed the absence of family violence patterns among the sample although they reported the observation of some sorts of fighting among their peers. The Researcher suggested further studies of other variables to determine the causes of the spread of deviant behavior. Furthermore, it recommended that parents provide their children with the proper religious upbringing, that the media, school curriculum developers and the guidance centers in the society to spread societal awareness, to monitor the symptoms of family violence, analyze them and deal with them according to the educational and social theories. Moreover, launching of social projects that provide social and financial services to the victims of family violence.
Keywords: domestic violence; deviant behavior; middle school students; public schools; Saudi Arabia